Lake Morphometry and its Effect on Aquatic Vegetation under the Influence of Eutrophication in Kashmir Waters: Lake Morphometry Influences Water Quality and Macrophyte Growth - Sobiya Gul; Adnan Abubakr; Syed Nadima Hilal Qadri (Fishery Technology, 2024)
The morphology plays a major role in a lake system’s water quality. The lacustrine structure and function has been shown to be significantly influenced by lake morphology. The current paper aims to examine the relationship between the physicochemical criteria of water and aquatic macrophyte distribution. Over the course of a year (September 2022-Oct 2023) data on the morphology, aquatic vegetation and water quality of two lakes was collected. To identify potential correlations between lake morphology features, key water quality parameters and macrophytes distribution, statistical and ordination analysis was carried out. Principal component analysis (PCA) was applied in order to distinguish the key morphological parameters and water quality parameters while Redundancy Analysis (RDA) was used in order to estimate possible associations between the macrophyte distribution and the morphology of the lakes. The results revealed significant correlations between the lake catchment area and total phosphorus concentration. The Lake catchment and depth key variables showed the strongest influence on the lake discrimination in the PCA results, followed by Schindler’s ratio. The RDA findings suggested that several macrophyte species may be grouped together in shallower lakes. The volume and depth of the lakes are characterized by a larger number of macrophytes. The RDA between hydrophyte data and water quality parameters revealed that the first three axes explained 84.97% of the species-environment relationship and 36.08% of the variance in the species data.